2D Materials: A Free‐Standing and Self‐Healable 2D Supramolecular Material Based on Hydrogen Bonding: A Nanowire Array with Sub‐2‐nm Resolution (Small 21/2017). Issue 21 (June 2017) - Li, Ming; Song, Mengyao; Wu, Guitai; Tang, Zhenyu; Sun, Yunfeng; He, Yunbin; Li, Jinhua; Li, Lei; Gu, Haoshuang; Liu, Xiong; Ma, Chuang; Peng, Zefei; et al.
Abstract : In article number1604077, by Ming Li, Yunbin He and co‐workers, demonstrate that hydrogen‐bonding (a weak and reversible interaction) can assemble conjugated polymer chains towards a free‐standing 2D material. The H‐bonding allows further splitting of the material into ribbons, which can re‐assemble, similar to a zipper, leading to the first example of a healable 2D material.